Evaluation of the In Vivo and In Vitro Effects of Fructose on Respiratory Chain Complexes in Tissues of Young Rats. (6th December 2015) - Macongonde, Ernesto António; Vilela, Thais Ceresér; Scaini, Giselli; Gonçalves, Cinara Ludvig; Ferreira, Bruna Klippel; Costa, Naithan Ludian Fernandes; de Oliveira, Marcos Roberto; Avila, Silvio; Streck, Emilio Luiz; Ferreira, Gustavo Costa; Schuck, Patrícia Fernanda
Abstract : Hereditary fructose intolerance (HFI) is an autosomal-recessive disorder characterized by fructose and fructose-1-phosphate accumulation in tissues and biological fluids of patients. This disease results from a deficiency of aldolase B, which metabolizes fructose in the liver, kidney, and small intestine. We here investigated the effect of acute fructose administration on the activities of mitochondrial respiratory chain complexes, succinate dehydrogenase (SDH), and malate dehydrogenase (MDH) in cerebral cortex, liver, kidney, and skeletal muscle of male 30-day-old Wistar rats. The rats received subcutaneous injection of sodium chloride (0.9%; control group) or fructose solution (5  μ mol/g; treated group). One hour later, the animals were euthanized and the cerebral cortex, liver, kidney, and skeletal muscle were isolated and homogenized for the investigations. Acute fructose administration increased complex I-III activity in liver. On the other hand, decreased complexes II and II-III activities in skeletal muscle and MDH in kidney were found. Interestingly, none of these parameters were affected in vitro . Our present data indicate that fructose administration elicits impairment of mitochondrial energy metabolism, which may contribute to the pathogenesis of the HFI patients.